Dampak Kawasan dan Status Negara terhadap Pertumbuhan Ekonomi Negara-Negara Terdampak Covid-19 - Junaedi, Dedi; Salistia, Faisal; Hermaliana, Mia (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
The COVID-19 pandemic has had multi-sectoral impacts, including disrupting the economic growth of many countries. This study aims to analyze the impact of the COVID-19 pandemic, fiscal capability as well as regional differences and country status on the economic growth of the affected countries. The method used is a quantitative method with a saturated sample of 135 countries, and a regression analysis approach with dummy variables. The results showed that the variables of pandemic cases, exposure time, population, regional differences and country status differences affected the economic growth of the affected countries (R2 0.6373). If the pandemic is under control and there is no disparity in management between regions and between countries, then global economic growth has the potential to be positive at 0.18%. If state spending is increased, it has the potential to reduce the impact of economic contraction by 0.27%. The management of the pandemic in the Asian, American and African regions is significantly different from that in the Australian region. Poor countries are different from developed countries, but not different from middle-income countries, in managing pandemics in their regions. In relative terms, the impact of the pandemic in Asia, America and Africa is heavier than other regions.